Strategy for Countermeasures for Destructive Fishing in Makassar City Waters - Fadly Fadly; Muhammad Kasnir; Ihsan Ihsan; Asbar Asbar (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Destructive fishing is fishing activity using materials, tools or methods of fishing that can damage fish resources and the environment. This study aims to determine the strategies for coping with destructive gishing in Makassar City waters. This type of research is using a qualitative descriptive approach and a quantitative approach. A qualitative approach was carried out to determine the strengths, weaknesses, opportunities and challenges of the Makassar City Fisheries Service. Data collection techniques were carried out through observation, interviews, questionnaires and documentation. The results of the study show that there are five powers that are owned by the territorial waters of Makassar City in preventing destructive fishing, namely the laws and regulations that are standard, have supervisors who go directly to the community to carry out socialization, supported by adequate infrastructure, take a persuasive approach to former perpetrators not to carry out destructive fishing, provide infrastructure and facilities for environmentally friendly fishing. This research can be used in making decisions regarding destructive fishing in Makassar city waters, because previous research only focused on damage to natural resources.